1,25-Dihydroxyvitamin D3 effects on the regulation of the insulin receptor gene in the hind limb muscle and heart of streptozotocin-induced diabetic rats - Calle, Consuelo; Maestro, Begoña; García-Arencibia, Moisés (Scientific Research Publishing, 2013)
In the present study, we examine the effects of the treatment with 1,25-dihydroxyvitamin D3 [150 IU/Kg (3.75 μg/Kg) once a day, for 15 days] to non-diabetic and streptozotocin-induced diabetic rats. The results indicate that treatment with 1,25-dihydroxyvitamin D3 had minor effects in non-diabetic rats. The same treatment in streptozotocin-induced diabetic rats, although it did not correct the hyperglycemia and hypoinsulinemia induced by the diabetes, caused other actions that could mean beneficial effects on the amelioration of diabetes e.g., it avoided body weight loss, increased calcium and phosphorus plasma levels, and corrected the over-expression of the insulin receptor mRNA species of 9.5 and 7.5 Kb present in the hind limb muscle and heart of these animals. These genomic 1,25-dihydroxyvitamin D3 effects could involve transcriptional mechanisms of repression mediated by vitamin D response elements in the rat insulin receptor gene promoter. Using computer analysis of this promoter, we propose the -249/-235 bp VDRE (5’GGGTGACCCGGGGTT3’) with a pyrimidine (T) in the (+7) position of the3’half-site as the best candidate for negative control by 1,25-dihydroxy-vitamin D3. In addition, posttranscriptional mechanisms of regulation could also be implicated. Thus, computer inspection of the5’untranslated region of the rat insulin receptor pre-mRNA indicated the presence of a virtual internal ribosome entry segment whereas the computer inspection of the3’untranslated region localized various destabilizing sequences, including various AU-rich elements. We propose that through these virtual cis-regulatory sequences, 1,25-dihydroxyvitamin D3 could control the translation and stability of insulin receptor mRNA species in the hind limb muscle and heart of diabetic rats.
Keywords: 1, 25-Dihydroxyvitamin D3; Streptozotocin-Induced Diabetic Rats; Hind Limb Muscle; Heart; Rat Insulin Receptor Gene; Computer Analysis; Vitamin D Response Element; Posttranscriptional Processes